Motivating Learners Through Gamification and Educational Games - Chocha, Dinesh Rambhai; Panda, Avilash (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
In this paper, the author will present an argument on how gamification and educational games can be used to influence the motivation of learners in different classes of education. It uses empirical studies and theoretical approaches to analyzing the effect of game-based strategies on intrinsic and extrinsic motivations as well as the presence of important game elements to motivate players and the moderation impact of leaner attributes. The study also identifies challenges and makes recommendations on successfully integrating gamification and educational games into curriculum in order to maintain long-term motivation of learners.